The Socratic Dialogue Technique in Improving Self-Love as an Effort to Address Toxic Friendships in Students - Putri Ayu Nurjanah; Muya Barida; Sri Hartini; Aprilia Setyowati; Putri Ayu Nurjanah; Sri Hartini (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Toxic friendships need to be addressed to prevent them from harming students. Therefore, students need to develop self-love to survive toxic friendships. The purpose of this study was to determine the effectiveness of group counseling using the Socratic dialogue technique in improving self-love as an effort to address toxic friendships in eighth-grade junior high school students. This study used a quantitative approach with a pre-experimental method, a one-group pretest-posttest design. Data processing was performed using Statistical Product and Service Solution (SPSS) 27.0 for Windows. The sample consisted of six eighth-grade students in junior high schools in Yogyakarta, selected using purposive sampling, who were provided during group counseling services. Group counseling services utilized group dynamics to improve junior high school students' self-love so that they have awareness of toxic friendships. Data collection in this study used a psychological scale and analyzed by paired sample t-test. The results of the paired sample t-test, with a significance value of 0.001 (<0.05), indicated a significant difference between the pretest and posttest. The average scores before and after treatment showed an increase from 38 in the pretest to 79 in the posttest. This improvement demonstrates that group counseling using the Socratic dialogue technique has a significant impact, with students becoming more able to understand and appreciate themselves, as well as being more discerning in their relationships. The results of this study indicate that group counseling using the Socratic dialogue technique is effective in improving students' self-love.